Optimization study of media creation ideas based on the new media environment - Zhao Hui wen; Tian Yi nong (SHS Web of Conferences, 2023)
Nowadays, new media are being used in more and more fields, most notably in the communication industry, with endless online media and ever-evolving cell phone terminals appearing in our lives all the time and becoming an essential part of our lives. Under the influence of this background, the creation and dissemination of art have gradually become dependent on new media and have begun a profound transformation. On the one hand, the new media has promoted the circulation of art, making the originally niche art categories to the mass market; on the other hand, the expanding market and audience also play an important role in influencing art creation. Therefore, the creative thinking of art creators nowadays will also change accordingly with the change of the background of the times.